2014
DOI: 10.1186/1471-2334-14-232
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for influenza-like-illness in the UK: online surveillance using Flusurvey

Abstract: BackgroundInfluenza and Influenza-like-illness (ILI) represents a substantial public health problem, but it is difficult to measure the overall burden as many cases do not access health care. Community cohorts have the advantage of not requiring individuals to present at hospitals and surgeries and therefore can potentially monitor a wider variety of cases. This study reports on the incidence and risk factors for ILI in the UK as measured using Flusurvey, an internet-based open community cohort.MethodsUpon ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 19 publications
1
74
0
1
Order By: Relevance
“…One found that public transport used within 5 days of symptoms onset was associated with an increased risk of consulting for acute respiratory infection [31]. Previous Influenzanet works did not find an association between public transport and influenza [16, 21, 32], likely because of lack of statistical power due to the consideration of one season only [16, 21] or due to methodological differences based on the public transport covariate definition [32]. In this last article, the public transport covariate was defined using three categories (bicycle/foot, car and public transport), whereas here we opted for two categories (private vs. public transports) in order to better observe any impact of public transports with respect to other modes of daily locomotion, where individuals do not have close contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One found that public transport used within 5 days of symptoms onset was associated with an increased risk of consulting for acute respiratory infection [31]. Previous Influenzanet works did not find an association between public transport and influenza [16, 21, 32], likely because of lack of statistical power due to the consideration of one season only [16, 21] or due to methodological differences based on the public transport covariate definition [32]. In this last article, the public transport covariate was defined using three categories (bicycle/foot, car and public transport), whereas here we opted for two categories (private vs. public transports) in order to better observe any impact of public transports with respect to other modes of daily locomotion, where individuals do not have close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…For the risk factors analyses, we considered the ILI definition of the European Centre for Disease Control and Prevention (ILI ECDC ), which is often used by other Influenzanet studies [16, 21, 22]. ILI is defined as (i) the sudden onset of symptoms, AND (ii) at least one of the following four systemic symptoms (fever or feverishness, malaise, headache or myalgia), AND (iii) at least one of the three respiratory symptoms (cough, sore throat, shortness of breath) [23].…”
Section: Methodsmentioning
confidence: 99%
“…risk-taking) as a response to a hypothetical low-efficiency HIV vaccine. In Adler et al [2] an Internet survey is used to assess the incidence and risk-factors associated with Influenza-like-illnesses. In this study a slightly higher incidence risk was measured for the female cohort which suggests that it may be worthwhile to study epidemic models that involve both risk behaviour and gender structure.…”
Section: Discussionmentioning
confidence: 99%
“…This participatory form of surveillance provides epidemiological information directly from the general population, including individuals who do not seek health care treatment following an infection. Even though the sample of self-selected individuals is usually not representative of the general population [4], the information collected in a participatory fashion can help determine risk factors [5] and have a better overview of healthcare seeking behavior and vaccination effectiveness [6]. In this paper we want to evaluate the performance of this web-based participatory surveillance system in combination with the sentinel doctor surveillance as a tool for improving the national surveillance of Influenza-like illness.…”
Section: Introductionmentioning
confidence: 99%